Study of antagonistic capability of liquid culture filtrate of isolate of Trichoderma harzianum against some plant and human pathogenic fungi - Yaziji, Maysa (Latakia University Journal -Biological Sciences Series, 2013)
The antagonistic activity of liquid culture filtrate of Trichodermaharzianum at different concentrations (5, 10, 20 and 30%) was evaluated "in vitro" at 25 C˚ against following plant and human pathogenic fungi: Aspergillusniger, Rhizopusstolonifer, Fusariumoxysporum, F.moniliforme, Alternariaalternata and Candida albicans. The results showed high level activity of culture filtrate inhibiting the growth of tested fungi. The activity was varied with the different species of fungi and the different concentrations of culture filtrate. The highest activity was against fungus A.niger which showed precent inhibition equal 96.3% at 30% concentration. Whereas the lowest inhibition percentage to 77.6% was recorded for fungus A.alternata in comparison with other fungi. The culture filterate was not affected the radial colonies growth of R.stolonifer at 5% and 10% concentrations, however the colonies was fragile and weak, and clearly inhibited the spores formation. The culture filtrate was showed high antagonistic capability against the human pathogenic fungus C.albicans, and the radial inhibition growth was 1.38 cm at 30% concentration.